KREATOR VIDEO DAKWAH INSTAGRAM: KAJIAN TERHADAP AKUN FUADBAKH - Romario Romario (Universitas Islam Malang, 2021)
Social Media as a free space provides freedom for anyone to fill in the contents and writings, this also does not escape the use of the Islamist movement which massively utilizes social media to embed ideas. Various kinds of social media platforms such as Facebook, WattApp, Twitter, Youtube, and Instagram are utilized by filling in content and lectures from Islamic clerics who have radical narratives. In this study, I will focus on how the Fuadbakh account that posts religious narratives by cutting the video of the interpreter and various edited videos. The account was chosen in popularity among teenagers as a content creator who made religious videos. In this study, I will explore the profile of Fuadbakh who has 1 million followers and 1,750 potentials, and removes several posts from the Fuadbakh account. The results of this study show short video posts from Fuadbakh, many made to discuss political issues, especially those that intersect with religion, video clips are usually taken from television shows such as ILC which are then combined with other texts and videos.